Internet Gaming Addiction among High School Students in Kendawangan against Sleep Quality and Learning’s Motivation - Iman Permana; Retnosari Retnosari (Ahmad Dahlan Medical Journal, 2021)
With the advance of information technology internet gaming has been showing to increase globally and across Indonesia. This phenomenon has been correlated to the decreasing the quality of sleep as well as learning motivation, and academic performance. This study aimed to analyze the relationship between gaming addiction and sleep quality and learning motivation among high school students in Kendawangan. A cross-sectional study was conducted among 33 high school students using questionnaires to assess the quality of sleep, motivation and gaming addiction. Results showed almost a quarter of sample were highly addicted. There was a significant relationship between gaming addiction and sleep quality (p 0.002, p<0.05) as well as with learning motivation (p 0.002, p<0.05). Thus, gaming addiction influenced quality of sleep and learning motivation among the high school students.